Pengaruh Peran Kepala Sekolah dan Iklim Organisasi Terhadap Produktivitas Kerja Guru pada SMP Se-Kecamatan Batanghari Lampung Timur - Ita Evina (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This study aims to determine (1) the influence of school principal's role on teacher work productivity, (2) organizational climate influence on teacher work productivity, and (3) influence of principal role and organizational climate together to productivity of junior high school teacher Kecamatan Batanghari Kabupaten Lampung Timur, as many as 170 teachers, were used as research samples of 63 teachers and 20 teachers of sample experiments outside the specified sample. Instruments used in the form of questionnaires previously tested for validity and reliability. Data analysis using Regression analysis.Based on the analysis, the following results are obtained: 1) The role of principal contributes to teacher work productivity of 3.2%; 2) Organizational climate contributes to teacher work productivity of 21.6%; and 3) Roles of school principals and organizational climate together contributes to teacher work productivity of 13.5%. The conclusion is taken that the productivity of junior high school teachers in Kecamatan Batanghari Kabupaten Lampung Timur will increase, which is influenced by the effective role of headmaster along with the conducive organizational climate applied.